Influence of Film Role on the Positive Development of College Students’ Entrepreneurial Behavior Using Positive Psychology - Zhang, Hang; Long, Huizhen; Chen, Yinchang (Frontiers in Psychology, 2022)
To help College Students improve their entrepreneurial psychology and enrich their innovative achievements, this paper investigates College Students’ entrepreneurial behavior based on the theory of positive psychology under the background of multiculturalism. Firstly, the background and development status of multiculturalism are expounded, and the main features of the multicultural era are pointed out; Secondly, the current situation is explained for College Students’ mental health and entrepreneurial behavior, and the specific connotation of College Students’ entrepreneurial psychology is summarized according to entrepreneurial behavior, including entrepreneurial consciousness, entrepreneurial will, entrepreneurial capability, and entrepreneurial personality; Thirdly, the positive effects of inspirational films and roles on the psychology of College Students are discussed. From the connotation of film and television culture, the main features of films are reviewed: intuitiveness, immediacy, universality, entertainment, and orientation. Finally, according to the psychological impact of inspirational films on College Students, a Questionnaire Survey (QS) is designed and distributed among the local College Students, and assumptions are put forward. The results show that the differences of College Students’ entrepreneurial level are mainly reflected in gender, urban, and rural household registration, only-child-or-no, and entrepreneurial experience, and the gender differences are mainly in entrepreneurial consciousness, will, and personality (p < 0.05); There are significant differences in consciousness, will, capability, and personality between urban and rural household registration and entrepreneurial experience (p < 0.05); The differences between the only-child and non-only-child are obvious in three aspects: will, capability, and personality (p < 0.05). After the intervention of inspirational films, the average scores of all dimensions of the entrepreneurial level of students in the intervention group are 35.45, 36.41, 38.17, and 37.22, respectively, which have a certain improvement compared with the situation before the intervention. There are significant differences in the four dimensions (p < 0.05), which is statistically significant, indicating that the intervention of inspirational films has a positive impact on students’ entrepreneurial level.